ANALISIS KESTABILAN PENGONTROLAN DUA POSISI PADA TANGKI BERINTERAKSI MENGGUNAKAN METODE DESCRIBING FUNCTION - Purwandito Tulus Asmoro (Jurnal Elektra, 2019)
A water storage unit consisting of 3 interacted tanks, the operation will experience problems if using manual control, because if manual control is not optimal, then when filling the water in the three tanks will cause water overflow which results in a lot of wasted water. Two- position control or "On-Off" is an appropriate control system applied to the water level setting in the tank storage unit. In a two-position control system, if the frequency of the rise and fall of water (Limit Cycle) is large, it will cause an increase in the number of "On-Off" switches and selenoid valve operations per minute, so the system becomes unstable, and will shorten the life component durability. The Describing Function (DF) method is an analytical method that can determine the Limit Cycle frequency based on the width of the water rise and fall distance (hysteresis) of a two position control system, with the aim of determining the hysterical parameters that cause the system to become stable.